2013
DOI: 10.4258/hir.2013.19.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Medication Adherence in Elderly Patients with Chronic Diseases Using Support Vector Machine Models

Abstract: ObjectivesThe aim of this study was to establish a prediction model of medication adherence in elderly patients with chronic diseases and to identify variables showing the highest classification accuracy of medication adherence in elderly patients with chronic diseases using support vector machine (SVM) and conventional statistical methods, such as logistic regression (LR).MethodsWe included 293 chronic disease patients older than 65 years treated at one tertiary hospital. For the medication adherence, Morisky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
4
28
0
3
Order By: Relevance
“…In another study Lee et al [12] compared SVM and LR for the classification of chronic disease and showed that SVM achieved higher accuracy with a smaller number of variables than the number of variables used in LR (71.1% for LR and 97.3% for SVM), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In another study Lee et al [12] compared SVM and LR for the classification of chronic disease and showed that SVM achieved higher accuracy with a smaller number of variables than the number of variables used in LR (71.1% for LR and 97.3% for SVM), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Son et al [11] compared various kernel functions in the SVM technique for predicting medication adherence in heart failure patients. In another study conducted by Lee et al [12], the performance of SVM was evaluated and compared with LR for the classification of chronic disease. In a study conducted by Lehmann et al [13], the performance of four classification methods (RF, SVM, NN, and LDA) were compared for recognition of Alzheimer disease.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Earlier studies reported that the rate of cost-related medication nonadherence among older adults was 5.4% in 2004 and dropped to 3.6% in 2006, likely representing the impact of the passage of the Medicare Modernization Act in 2003, which led to the full implementation of Medicare Part D in 2006. 15,18 Furthermore, while there are many studies reporting the prevalence of and factors associated with medication nonadherence, they are often outdated, [19][20][21] exclude older adults, 22,23 have limited generalizability, 21,24 or do not elicit cost-specific medication nonadherence and its reasons among older adults. 25,26 In comparison to younger individuals, older adults have an increased risk of medication nonadherence because of multiple chronic conditions and higher medication use.…”
mentioning
confidence: 99%
“…A study conducted in Nigeria also found that age, gender and education level did not impact medication adherence but the employment was a significant variable (Okuboyejo, 2014). Meanwhile a few studies have concluded that age and education level were significantly related to medication adherence in elderly patients with chronic disease and female patients were at increased risk for nonadherence to statins therapy (Lee et al, 2013;Lewey et al, 2013).…”
Section: Discussionmentioning
confidence: 99%